Numerical simulation of oxidative corrosion of metallic uranium in a confined environment with a validation through existing experimental data - Mengxian Xiang; Weiquan Liang; Ning Ma; Sizhi Zuo-Jiang; Xuzhou Jiang; Hongying Yu; Dongbai Sun (Journal of Materials Research and Technology)
As an energy source and strategic material, uranium usually needs to be stored in a confined environment for long periods of time. Due to its active chemical nature, uranium will inevitably corrode, thus affecting its performance. However, uranium is radioactive, making its degree of corrosion in confined environments difficult to measure in real time. In this paper, a three-dimensional transient oxidative corrosion model of uranium metal in a confined oxygen environment was established based on the finite element method, and the oxidation kinetics of uranium in different stages (parabolic stage, transition stage, linear stage, and decline stage) were modeled. The effects of temperature, initial pressure, and sample shape on the oxidative corrosion process of uranium were simulated, and the mechanism of corrosion was analyzed and discussed. The accelerating effect of temperature on the oxidation rate stems mainly from the increase in the reaction rate constant and the significant increase in the gas diffusion rate of confined environment. The higher the initial oxygen pressure, the longer the duration of the linear stage of uranium oxidation kinetics, and the more significant difference between the oxidation rates in the decline stage. Moreover, smaller specific surface area of the sample can slow down the process of oxidative corrosion, but the final oxide film thickness increases. The results provide the relationship between the growth of uranium oxide film thickness and the real-time oxygen pressure change in a confined environment, and provide a valuable reference for predicting the oxidative corrosion behavior of uranium during long-term storage.